Simon Gathercole's, Defending Substitution: Why I Am Unconvinced and Concerned. (July 2018) - Duke, Rodney K.
This article is a reflective review of Simon Gathercole's book, Defending Substitution, in which he defended the position that Paul held a substitutionary position of atonement. That position contends that Jesus died 'instead of sinners', replacing them in his death. I primarily offer an exegetical critique based on an Old Testament understanding of Paul's language, in which I do not find a mechanism of substitution. That critique is followed by some reflections on why I find Gathercole's substitutionary view to fall short of the portrayal of God's offers of grace and atonement that are found in the OT and picked up on by the New Testament writers as they use the OT language.